The fungal 9‐methyl‐sphingadiene is a novel ligand for both PPARγ and GPR120. Issue 5 (25th July 2018) - Esaki, Shota; Nagasawa, Tomotaka; Tanaka, Haruka; Tominaga, Aoi; Mikami, Daisuke; Usuki, Seigo; Hamajima, Hiroshi; Hanamatsu, Hisatoshi; Sakai, Shota; Hama, Yoichiro; Igarashi, Yasuyuki; Kitagaki, Hiroshi; et al.
Abstract: 9‐Methyl‐sphingadiene has a characteristic structure containing a methyl group and is only found in fungi including mushrooms and mycota such as Aspergillus oryzae . The Japanese daily ingest it through traditional fermented foods, such like miso, soy sauce, and sake. However, the food function of 9‐methyl‐sphingadiene is hardly elucidated. In this study, we first revealed that 9‐methyl‐sphingadiene is a novel ligand for peroxisome proliferator‐activated receptor γ (PPARγ) and GPR120, and induces differentiation in 3T3‐L1 cells. Synthetic ligands of PPARγ are widely used to treat type 2 diabetes, and are known to accelerate adipogenesis. GPR120 plays an important role in the browning of adipocytes and their differentiation into beige cells. An increase in beige cells and brown adipocytes is known to suppress obesity. Thus, ligands for PPARγ and/or GPR120 are thought to have important function in controlling diabetes and obesity. Our result indicates that fungal sphingoid bases in fermented foods have anti‐diabetic role. Practical applications One major characteristic of Japanese meal is to use various food fermented with the non‐pathogenic fungus Aspergillus oryzae, Koji . The Koji contains unique sphingoid base, 9‐methyl‐sphingadiene. In this study, we investigated a food function of the 9‐methyl‐sphingadiene, and found that 9‐methyl‐sphingadiene is a novel ligand for PPARγ and GPR120. Since the ligands of PPARγ and GPR120 are involved in anti‐obesity and anti‐diabetes, our result indicates that daily intake of Koji might prevent the development of obesity and diabetes. This study do not only reveals one of the health benefit of Japanese food containing Koji, but also the possibility in the application of 9‐methyl‐sphingadiene as functional food.